Urticaria-angioedema complicated by intussusception. - Kalenahalli Jagadish, Kumar; Bellam Manvi, Chowdary; Sudhamshu Kalasapura, Chandrashekar; Manjunath Vaddambal, Gopalkrishna (European Journal of Pediatric Dermatology, 2025)
Angioedema is abrupt swelling of the skin involving the deeper layers of the sub dermis and classically affects lips and eye(periorbital). It can involve mucous membranes of upper respiratory and gastrointestinal tracts also. Acute angioedema attacks can be mast cell-mediated ( histaminergic) or bradykinin-mediated. In histaminergic angioedema, the signs and symptoms include urticaria, flushing, generalized pruritus and bronchospasm. Bradykinin mediated angioedema examples like hereditary angioedema (HAE) typically present without symptoms of pruritus or urticaria. They commonly present with gastrointestinal symptoms which include nausea, vomiting, diarrhea, abdominal pain and rarely intussusception which are the result of bowel wall edema. However in histaminergic angioedema, intussusception is not reported. We present a case of mast cell-mediated( histaminergic) angioedema in a 14 year old boy who presented with urticaria, flushing, generalized pruritus and bronchospasm later developed prominent GIT symptoms with intussusception. He had intermittent transient intussusception confirmed by sonography and responded to pneumatic reduction.